2021
DOI: 10.1016/j.hemonc.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ventricular dysfunction in Egyptian children with Beta-thalassemia major

Abstract: Objective/Background: The purpose of this study was to evaluate serum cardiac troponin I and serum N-terminal (NT) pro-brain natriuretic peptide (pro-BNP) levels and the utility of tissue Doppler imaging in assessing cardiovascular changes following left ventricular (LV) dysfunction in children with beta-thalassemia major (β-TM). In children with β-TM who depend on regular blood transfusion, cardiac iron toxicity is a common serious complication. The most common cause of death among these patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
2
10
0
3
Order By: Relevance
“…Higher LV early diastolic filling and a high E/A ratio in this case study indicated a restricted [11]. This was also in line with a prior analysis that stated that the most common finding in individuals with TM is a high E/A ratio [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Higher LV early diastolic filling and a high E/A ratio in this case study indicated a restricted [11]. This was also in line with a prior analysis that stated that the most common finding in individuals with TM is a high E/A ratio [12].…”
Section: Discussionsupporting
confidence: 92%
“…In Table 1 descriptive statistics of all quantitative variables was calculated in term of mean and standard deviation. Mean age of the patients was 10.60±4.064 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant (p<0.05) increase in plasma BNP levels in TDT patients than controls with normal EF in the current study. These results are also reported by Kremastinos et al 2007 31 and Deraz et al 2021, 32 who found significantly (p<0.05) high levels of BNP with no clinical presentation of heart failure (HF) nor abnormal EF.…”
Section: Discussionsupporting
confidence: 82%
“…Currently, there is no effective treatment for severe beta thalassemia; however, regular blood transfusions and iron removal are used clinically to prolong the lives of children. Despite these interventions, it is still difficult to avoid direct death due to liver and kidney damage as well as heart failure before puberty [ 11 ]. The majority of children with thalassemia major require long-term drug treatment and medical care after they are discharged from the hospital because the disease has a prolonged treatment course, repeated conditions, and many complications.…”
Section: Discussionmentioning
confidence: 99%